2018
DOI: 10.1016/j.bja.2017.12.039
|View full text |Cite
|
Sign up to set email alerts
|

A neurosteroid analogue with T-type calcium channel blocking properties is an effective hypnotic, but is not harmful to neonatal rat brain

Abstract: Background: More than 4 million children are exposed annually to sedatives and general anaesthetics (GAs) in the USA alone. Recent data suggest that common GAs can be detrimental to brain development causing neurodegeneration and long-term cognitive impairments. Challenged by a recent US Food and Drug Administration (FDA) warning about potentially neurotoxic effects of GAs in children, there is an urgent need to develop safer GAs. Methods: Postnatal Day 7 (P7) rat pups of both sexes were exposed to six (repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
85
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(101 citation statements)
references
References 46 publications
11
85
2
1
Order By: Relevance
“…3β-OH (3β,5β,17β)-3-hydroxyandrostane-17-carbonitrile and ent-3β-OH ent-[(3β,5β,17β)-3-hydroxyandrostane-17-carbonitrile] are a synthetic neurosteroid analogues synthetized using procedures that have been described in our previous publications (Atluri et al, 2018;Han, Zorumski, & Covey, 1996;Todorovic et al, 2004). ent-3β-OH was also produced from ent-testosterone (Hu et al, 1997) using the procedure reported for the preparation of 3β-OH from testosterone (Atluri et al, 2018). Morphine was purchased through University of Colorado Hospital Pharmacy (Morphine sulfate inj.…”
Section: Methodsmentioning
confidence: 99%
“…3β-OH (3β,5β,17β)-3-hydroxyandrostane-17-carbonitrile and ent-3β-OH ent-[(3β,5β,17β)-3-hydroxyandrostane-17-carbonitrile] are a synthetic neurosteroid analogues synthetized using procedures that have been described in our previous publications (Atluri et al, 2018;Han, Zorumski, & Covey, 1996;Todorovic et al, 2004). ent-3β-OH was also produced from ent-testosterone (Hu et al, 1997) using the procedure reported for the preparation of 3β-OH from testosterone (Atluri et al, 2018). Morphine was purchased through University of Colorado Hospital Pharmacy (Morphine sulfate inj.…”
Section: Methodsmentioning
confidence: 99%
“…We first examined the effects of 3 mM 3b-OH on well-isolated Tcurrents in CeM neurones from adolescent WT mice using acute brain slices as we have previously determined that this is a relevant brain concentration during hypnosis. 1 Representative current traces from a steady-state inactivation protocol are presented in Fig 1a. The left panel shows traces of inward Tcurrent of a CeM neurone under control conditions, and the right panel shows traces from the same neurone in the presence of 3b-OH, both recorded using a tetramethylammonium with adenosine triphosphate (TMA with ATP) internal solution. 3b-OH stabilised inactive states of the channel and shifted inactivation V 50 values of about e5 mV (Fig 1b).…”
Section: Voltage-dependent Inhibition Of T-currents By 3b-oh In Wt Micementioning
confidence: 99%
“…Moreover, no clearly superior injectable anesthetic has been identified. Most recently, the experimental neuroactive steroid 3β-OH has demonstrated anesthetic properties without neurotoxicity [ 63 ]. In summary, animal studies into comparable neurotoxicity have demonstrated widely conflicting results; therefore, no general anesthetic was consistently identified to be safer than others.…”
Section: Discussionmentioning
confidence: 99%